Exploring the significance of service quality on customer satisfaction, : a case study of DHL Express Zimbabwe (Private) Limited - Mamhunze, Talent (Midlands State University, 2020)
The research was carried out to determine the contribution of service quality on customer satisfaction, dwelling more on service tangibility – a variable for service quality. The research was based on DHL Express Harare (Airport). The objectives of the study were constructed from service tangibility with the aim of determining the contribution of packaging on customer satisfaction, the influence of personnel on customer satisfaction and the significance of equipment on customer satisfaction. The literature review looked at the following aspects which contributes positively to customer satisfaction: protection and preservation, communication and labeling, environmental soundness, convenience and aesthetics. Furthermore, employee training and employee engagement were also emphasized as instruments for customer satisfaction. The transportation, maintenance of warehouses including other company facilities and the tracking facility have also showed significance in satisfying customers. The researcher used both descriptive and explanatory research designs. A sample size of 16, 14 and 1 was used for customers, personnel and the management respectively. Questionnaires were used for the customers and interviews for the management as the research instruments. The research used both primary and secondary sources of data. Data gathered was presented using graphs and tables to illustrate the research findings and responses gathered. The findings of this research revealed that packaging, personnel and equipment have a positive impact on customer satisfaction and more of the customers proved to be satisfied. The study from the employee responses however showed that a lot has to be done by DHL Company in improving its fleet to ensure reliability and delivery of parcels in good condition. Overall, the results from the study evidenced that, service tangibility contributes more on customer satisfaction if the operational activities are executed properly by both the personnel and the management of DHL Company. The researcher recommended DHL Express to continue improving its quality services and to adopt some strategies to improve customer satisfaction through service quality such as service responsiveness, reliability, empathy and assurance.